Programas de apoio a micro e pequenas empresas em arranjos produtivos locais: a atuação do Sebrae-SP no pólo industrial de Franca-SP. - BARBOSA, Neida Terezinha Machado (109, 2011)
O objetivo fundamental deste trabalho é identificar, através de um estudo de caso por métodos qualitativos e quantitativos, a atuação do SEBRAE-SP e sua contribuição para o desenvolvimento das MPEs do Arranjo Produtivo Local - APL Calçadista de Franca e região, localizado no Estado de São Paulo. Especificamente, foca os serviços oferecidos, sua implementação e os resultados obtidos. Neste sentido, a partir da coleta dos dados, diagnosticaram-se os aspectos das ações SEBRAE neste pólo calçadista.

The main objective of this paper is to identify, through a study of case by qualitative and quantitative methods, the performance of SEBRAE-SP and its contribution to the development of the MSEs of the Local Productive Arrangement - LPA Footwear of Franca and region, located in São Paulo. Specifically, it focuses on the services offered, its implementation and the results obtained. Accordingly, from the collection of data, were diagnosed the aspects of the actions of SEBRAE in this shoe hub.
Support programs for micro and small companies in local productive arrangements: the performance of Sebrae-SP in the industrial pole of Franca-SP
Keywords: Calçados; Controle e Processos Industriais